2019
DOI: 10.1097/scs.0000000000005371
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Sinus Osteoma: From Direct Excision to Endoscopic Removal

Abstract: Frontal sinus osteomas are benign bone-forming neoplasms. Ongoing advancements in endoscopic surgery have allowed less invasive surgical approaches to be adopted for removal. The authors systematically reviewed the literature to provide analysis and recommendations for management. One hundred ninety-three publications encompassing 1399 patients met inclusion, with mean age 42.1 ± 13.8 years and a male predominance (59.2%). Symptoms included pain (70.8%); orbital/ocular (20.7%); sinonasal (36.4%); n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Therefore, we speculate that the short-term recurrence of case 2 osteoma may be related to the rate of growth and maturation of her bones. In addition, it has been reported that the incomplete resection of osteomas is also one of the reasons for recurrence 30 . However, despite complete removal of the osteoma at the time of the initial surgery, recurrence still occurred in the 2 cases emphatically reviewed in this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, we speculate that the short-term recurrence of case 2 osteoma may be related to the rate of growth and maturation of her bones. In addition, it has been reported that the incomplete resection of osteomas is also one of the reasons for recurrence 30 . However, despite complete removal of the osteoma at the time of the initial surgery, recurrence still occurred in the 2 cases emphatically reviewed in this study.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, it has been reported that the incomplete resection of osteomas is also one of the reasons for recurrence. 30 However, despite complete removal of the osteoma at the time of the initial surgery, recurrence still occurred in the 2 cases emphatically reviewed in this study. We conjecture that a possible reason for the recurrence of frontal osteoma in these 2 patients is that the microscopic osteoma cells isolated during the resection of the osteoma infiltrated into the adjacent periosteum or bone tissue, which provided a favorable condition for the recurrence of the osteoma.…”
Section: Discussionmentioning
confidence: 72%
“…These include the compact or ivory subtype, described as dense bone with areas of defined lucency; the mature or spongiosum type, described as heterogenous bone density similar to an area of fibrosis; or the mixed subtype, encompassing features of both main osteoma varieties. 86 A Tc-99m bone scintigraphy with emission computed tomography/CT can be used as an additional diagnostic tool. 87 On CT imaging, the nidus is often described as oval or round with peripherally low attenuation and an area of high attenuation centrally.…”
Section: Diagnosismentioning
confidence: 99%
“…There are a variety of histologic subtypes of osteomas that exist. These include the compact or ivory subtype, described as dense bone with areas of defined lucency; the mature or spongiosum type, described as heterogenous bone density similar to an area of fibrosis; or the mixed subtype, encompassing features of both main osteoma varieties 86 . A Tc-99m bone scintigraphy technique with single-photon emission computed tomography/CT can be used as an additional diagnostic tool 87 …”
Section: Diagnosismentioning
confidence: 99%
“…The most common symptom is headache, and others include nasal congestion, local pain, and ocular symptoms such as epiphora, exophthalmos, and visual field disturbance. In the case of an asymptomatic or small osteoma, regular follow-up is sufficient, but in the case of a symptomatic osteoma, surgical removal is generally performed as the primary treatment [4,5]. In this study, clinical features and imaging findings were analyzed in patients with osteoma confirmed by ostiomeatal unit (OMU) CT or PNS CT with a review of the existing literature.…”
Section: Introductionmentioning
confidence: 99%